1984
DOI: 10.1007/bf00021123
|View full text |Cite
|
Sign up to set email alerts
|

Additive gene action for resistance to Puccinia striiformis F.SP. Tritici in Triticum dicoccoides

Abstract: Triticum dicoccoides, wild emmer wheat. Puccinia striijbrmis, yellow rust, stripe rust of wheat, minor genes . SUMMARY Seven single-plant selections of wild emmer, with temperature-sensitive minor-effect genes for stripe rust resistance, were intercrossed in eight combinations . The resulting progenies were studied for a possible additive gene action .The transgressive segregation towards resistance in F 2 observed in all the combinations indicates that additive gene action for resistance indeed occurs in wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Various crossing programmes, to study further characteristics and combining ability of the temperature-sensitive genes in wild emmer, are in progress . One of the characteristics of minor effect genes in T. aestivum, namely additive gene action, has been investigated also in T. dicoccoides (GRAMA et al, 1984) .…”
Section: Resultsmentioning
confidence: 99%
“…Various crossing programmes, to study further characteristics and combining ability of the temperature-sensitive genes in wild emmer, are in progress . One of the characteristics of minor effect genes in T. aestivum, namely additive gene action, has been investigated also in T. dicoccoides (GRAMA et al, 1984) .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore a number of wild emmer entries were included in the present study which in previous work had proved to possess different temperature-sensitive genes (Grama et al ., 1984) . Having had no previous 11 Entry No .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally believed that race-specific resistance is not very durable, in this case, where we deal with genes which are both race-specific and additive in action (Grama et al ., 1984), there seems to be a better chance for stability . Parlevliet & Zadoks (1977) compared the level and durability of resistance based on race-specific minor genes with additive effects with that of resistance based on true race-non-specific minor genes with additive effects .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In later work it was shown that numerous selections of wild emmer were highly resistant to isolates of yellow rust from many countries (Van Silfhout and Gerechter-Amitai, in preparation). In addition to this 'seedling' or overall resistance conferred by major genes, Gerechter-Amitai et al (1984) described in wild emmer also another kind of resistance conferred by temperature-sensitive 'minor-effect' genes, which are race-specific (Gerechter-Amitai and Van Silfhout, in press) and, when combined, display additive gene action (Grama et al, 1984). Gerechter-Amitai et al (1984) concluded that these genes are effective not only in the seedling stage but also in the adult-plant stage, in the field.…”
Section: Introductionmentioning
confidence: 96%